Motivation among Indonesian Nurses in Pursuing Continuing Professional Education and Its Relationship to Their Competencies - Suangga, Fitriany; Tuppal, Cyruz P. (Nurse Media Journal of Nursing, 2017)
Background: Nurses are required to maintain the standards of their practice through an informed range of Continuing Professional Education (CPE). However, there is a paucity of evidence exploring the relationship between motivation in pursuing CPE and competency among Indonesian nurses.Purpose: This descriptive correlational study describes the motivation among Indonesian nurses in pursuing CPE and its relationship to their competency outcome performance.Methods: Ninety-three staff nurses were chosen by convenience sampling, informed and gave consent for their voluntary participation in a selected hospital in Jakarta, Indonesia. Before the data collection, the researchers sought ethical clearance from the respective organizations. Eligible participants were those who have at least one-year hospital experience, naturally born Indonesian, and completed a degree in nursing. Data were collected using adapted, pilot-tested, translated, and validated sets of questionnaires.Results: The findings revealed that most of the nurses were 21–30 years old, married, permanent employees with 1–3 years’ working experience and had earned a degree in nursing. Indonesian nurses had moderate to high motivation in pursuing CPE and exemplified a fair to very good level of competency outcome performance. Results also indicated that among the motivation factors, expectancy was significantly associated with critical thinking (r=0.259, p< 0.012).Conclusion: Motivation among Indonesian nurses in pursuing CPE was at a moderate to high level. As Indonesia emerges as a promising country, leaders need to increase the motivation of nurses in their pursuit of CPE. Highly competent and well-prepared nurses can facilitate a caring and healing environment for patients and contribute to the overall performance of health-care organizations and society.